Relationships between fatigue severity scale (FSS)/ scale for mood assessment (EVEA) and clinical manifestations in spanish long-COVID patients. - Esther Bahillo Ruiz; Lucía Pérez-Pérez; Rosa M Cárdaba-García; Carlos Durantez-Fernández; Lourdes Jiménez-Navascués; Veronica Velasco-Gonzalez; Alba Muñoz-Del Caz; Miguel Madrigal; Elena Olea (PLoS ONE)
Aim This study aims to investigate the influence of fatigue and mood disturbances in Spanish long-COVID patients and to establish relationships between these factors and other clinical manifestations. Method A descriptive correlational study was conducted using a self-administered online questionnaire. The sample was obtained through non-random convenience sampling, comprising 374 participants from various regions of Spain. Data collection occurred between July 2, 2022, and November 30, 2022. The questionnaire collected demographic information and inquired about symptomatology as well as self-perception of health status. Validated scales, namely the Fatigue Severity Scale (FSS) and the Scale for Mood Assessment (EVEA), were utilized. Results The non-random sample consisted of 374 participants from diverse regions of Spain, of whom 79.9% were women. Over 70% of participants reported fatigue, while the EVEA revealed high scores in sadness-depression (4.94 ± 2.82) and anxiety (4.57 ± 2.88). Significant relationships were identified between fatigue and mood disturbances and neurological, psychological, locomotive, and pain symptoms. Conclusions Given the impact of the syndrome on psychological, social and economic spheres, regular monitoring of patients with long COVID is crucial. This study corroborates previous research findings and is notable for demonstrating the persistence of symptoms for over a year. Mood disorders, such as anxiety and depression, are closely related to physical symptoms, highlighting the need for holistic healthcare approaches.